Paving towards a high income advance economy through NKEA - Abdul Hamid, Khalid; Abdul Rashid, Zakariah (2011)
There are a large number of sceptics that tends to contemplate the country’s inability to leap out of its middle income trap.Also, there exist claims with revealing prove exposing Malaysia’s incapability in coming out of this lock-in. With the challenge to prove otherwise, this paper tries to shed some light on whether the NKEA as one part of the NEM could transform the already rapid growing economy into a high income advance economy as desired and aspired by many. Since the NEM covers a broader dimensions covering inclusiveness and sustainability to meet developed nation criteria, in pursuant to be more focus and objective, the heart of this paper rest on high income achievement. Initially, we compared several human development indices to gauge the present inclusiveness and sustainability of the country. Subsequently, we employ the input-output-based methodology supported by the latest Malaysian Input-Output Tables 2005, to estimate linkages and multipliers as basic tools to uncover the strength and magnitude of the Malaysian economy’s transformation. We found some inclusiveness indicators illustrate considerable signs of a developed nation, however, great challenges will still have to be faced under sustainability dimension, probably compromised by favouring more towards high income percapita. Further, prospective growth in income is comparatively easier to achieve than sustainability since there exist huge potential in pursuing best practices from developed countries in terms of technology and productivity that could enhanced economic development in paving the way through trajectory transformation, but at what price.